Amelin: a 4.1-related spectrin-binding protein found in neuronal cell bodies and dendrites - Krebs, KE (J Neurosci, 1987)
An immunoreactive, structural, and functional analog of erythrocyte protein 4.1 is present in neuronal cell bodies and dendrites. Other investigators have described the isolation of a 4.1 analog in brain with structural characteristics suggesting that its identity was synapsin I, a neuronal phosphoprotein localized in the presynaptic terminal in association with small synaptic vesicles. In this report we demonstrate that the cell body/dendritic form of brain protein 4.1, which we have named amelin, is distinct from that of synapsin I on the basis of subcellular localization, migration in 2-dimensional gel electrophoresis, and structural criteria. We also demonstrate that amelin, like synapsin I, can bind brain spectrin on nitrocellulose paper. Neither amelin nor synapsin I binds calmodulin, as determined by a blot binding assay. We hypothesize that there exists in brain a family of 4.1-related proteins with distinct subcellular localization and function.